Integration of multi-sensor remote sensing, geological and geochemical data for delineation of Pb–Zn bearing carbonates of Middle Aravalli group in Zawar–Dungarpur Belt, NW India. Issue 27 (13th December 2022) - Jain, Ronak; Bhu, Harsh; Kumar, Hrishikesh; Purohit, Ritesh
Abstract: The rocks of the Aravalli Protocontinent of NW India are enriched in lead–zinc bearing deposits amongst which the Zawar mineralized belt is one of the famous for base metal deposits and was mined since ancient times. In the present study, an attempt has been made to identify and map the extension of the mineralized belt and base metal prognostic zones using the integration of multi-sensor remote sensing, geological and geochemical data. Remote Sensing studies were carried out using ASTER, AVIRIS-NG, and ASAR datasets to understand the extension and associated structural features of host rocks (dolomite in the present case) of lead–zinc mineralization from the Middle Aravalli Group. Relative band depth (B6 + B9/B8) was used to delineate the dolomite of the region using the ASTER imagery. Mineral map was derived using the AVIRIS-NG dataset with the help of the MTMF algorithm. Multifrequency and multipolarization ASAR datasets demarcated the structural features in the complexly deformed rocks of the extended belt. The obtained results from remote sensing were validated with the help of geological and geochemical studies. Geological studies (field surveys and petrographic studies) confirmed the presence of dolomites and associative mafics. Mineralogical, major oxides and trace elements data further substantiated the presence of dolomite, associated sulfides such as galena, sphalerite, pyrite, and chalcopyrite, and lead, zinc and copper in the Zawar–Dungarpur Belt. Presence of chromium and nickel were observed through the trace element studies of dolomite belt. The trace elements interpolated maps were superimposed by traced structural maps using ASAR datasets. The densely populated E-W lineaments are considered the suitable zones for base metal accumulation. These lineaments carried the base metal bearing fluid along with a low concentration of Chromium and Nickel. Under the finding of this study, the northern head of Hati Magra and near Keekawat are the suitable zones for Pb–Zn sulfide mineralization.